SYNTHESIS OF HIERARCHICALLY POROUS SSZ-13 ZEOLITE VIA PARTIAL DETEMPLATION-DESILICATION METHOD - KUSUMA WARDANI (NIM: 20515052), MARYANI
SSZ-13 zeolite has typical pore architecture arranged by a large ellipsoidal cage (cha) with dimension 7,3 Å x 12 Å and double six-membered ring (d6r) with dimension 3,8 Å x 3,8 Å as composite building units. This material has shown remarkable catalytic activity in MTO (methanol-to-olefin) reaction and selective catalytic reduction of NOx (NH3-SCR) due to their high selectivity toward reactant and product molecules. However, SSZ-13 tends to undergo faster deactivation because of diffusion hindrance due to solely presence of micropores. There have been strong evidences that the rapid deactivation in zeolite can be suppressed by hierarchically porous zeolite. To date, synthesis of hierarchically porous SSZ-13 zeolite are using bottom-up and top-down method. Bottom-up method using additional mesoporogen such as soft template or hard template. Since the mesoporogen not environmentally benign due to the increased carbon emission and it is not commercially available and, thus, should be synthesized through a series of complex organic reactions. Alternatively, top-down method such as desilication and or dealumination have been used to introduce mesopores within zeolite structure. This unexpected yet interesting results are explained by substantially loss of crystallinity due to the uncontrol silicon-extraction during desilication. New strategy is recently discovered to control mesopores formation beta zeolite by partial detemplation-desilication method. For the first time, partial detemplation-desilication is applied in hierarchically porous SSZ-13 zeolite formation. The obtain mesoporous SSZ-13 shows comparable hydrothermal stability and hot-liquid water stability to that of purely microporous parent SSZ-13. The vary of calcination temperature have been done to control organic contain in zeolite framework to parallelly study about its ability to protect siloxane bond from hydroxyl ion during desilication. Based on X-rays diffractograms, the typical peaks of SSZ-13 zeolite appear in AS-AT-C550 and C250-AT-C550 samples. The decreasing of organic contain at the C450-AT-C550 and C550-AT-C550 leads to the disappear of typical peaks that shown amorphous behavior. Additional characterizations such as IR-ATR, Raman, SEM, TEM, XRF, 29Si and 27Al MAS NMR were used to support the XRD data. Based on the data, it can be concluded that partial detemplation plays a critical role to control desilication rate in mesoporous SSZ-13 zeolite formation. The stable crystallinity of SSZ-13 zeolite product after hydrothermal and hot-liquid water testing shows the zeolite products have relative high stability upon those conditions.